1996
DOI: 10.1021/ed073p940
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Devices: Solid-State Refrigerators and Electrical Generators in the Classroom

Abstract: Thermoelectric devices provide an engaging high-tech demonstration suitable for illustrating thermodynamic principles in the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…37 A key reason to employ NS TE materials is to have a low k due to extensive phonon scattering at the grain boundaries. 38 The measured k (Fig. 7(d)) of the sample shows lower values than that of bulk ingot Bi 2 Te 3 (1.5 W mK À1 ).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…37 A key reason to employ NS TE materials is to have a low k due to extensive phonon scattering at the grain boundaries. 38 The measured k (Fig. 7(d)) of the sample shows lower values than that of bulk ingot Bi 2 Te 3 (1.5 W mK À1 ).…”
Section: Resultsmentioning
confidence: 79%
“…It has been reported 39 that porosity might have played an important role which can be deduced by the low electrical conductivity. 38 Thus, the sufficient densification with smaller grain size decreases k, enhances s and S, giving really a high s/k for nanostructured Bi 2 Te 3 sintered by SPS, especially in the low temperature region. Thermal conductivity, k, is composed of lattice thermal conductivity, k L , and electronic thermal conductivity, k e (k ¼ k L + k e ).…”
Section: Resultsmentioning
confidence: 98%
“…However, typical thermoelectric semiconductor materials including bismuth telluride are expensive, chemically unstable and relatively difficult to process, yielding the limited use for thermoelectric devices. 3,4 More recently, the thermoelectric property of graphene and its derivatives became a rising research topic because of the promising performances and tailorability. Previous theoretical works on the thermoelectric property of graphene demonstrated that the calculated ZT could be as high as 4 with Seebeck coefficient of more than 500 μV/K.…”
Section: Introductionmentioning
confidence: 99%
“…1, is constructed of an array of p-type and n-type TE columns bonded between two ceramic plates [6]. These columns are connected electrically in series to form a chain of p-n junctions but thermally in parallel.…”
Section: Introductionmentioning
confidence: 99%